DIAGNOSTIC TEST OF POLYNEUROPATHY SCORE, 10-G SEMMES WENSTEIN MONOFILAMENT (SWM) AND VIBRATION PERCEPTION TRESHOLD (VPT)-QUANTITATIVE SENSORY TESTING (QST) IN DISTAL SENSORY POLYNEUROPATHY (DSP)-HUMAN IMMUNODEFICIENCY VIRUS (HIV) - Purbasari, Bethasiwi; Kurniawan, Shahdevi Nandar; Husna, Machlusil; Candradikusuma, Didi; Al-Rasyid, Harun (Malang Neurology Journal, 2019)
Background: HIV/AIDS is a worldwide pandemic. Peripheral neuropathy is the most common neurologic complication with distal sensory polyneuropathy (HIV-DSP) as the most frequent form of manifestation. HIV-DSP is one of the major causes of global pain morbidity and often undiagnosed earlier, resulting in treatment given when HIV-DSP grade is already severe. Early detection is imperative to prevent the progression of HIV-DSP and improve patient’s quality of life. Polyneuropathy score, 10-g Semmes-Weinstein Monofilament (SWM) and vibration perception threshold (VPT)-quantitative sensory testing (QST) are considered to be potential candidates for HIVDSP screening tool.Objective: To measure the reability of Polyneuropathy Score, SWM and VPT- QST in diagnosing HIV-DSP.Methods: This research is a descriptive study with cross-sectional design. Research was conducted on 77 patients of HIV/AIDS outpatient clinic in RS Saiful Anwar (RSSA) during November 2016 - April 2017 (n = 77). Patients were screened for HIV-DSP by using polyneuropathy score, such as: Michigan Neuropathy Screening Instrument (MNSI), Toronto Clinical Scoring Sysytem (TCSS), Brief Peripheral Neuropathy Score (BPNS), SWM, and VPT-QST. Sensitivity, specificity, positive predictive value and negative predictive value of BPNS, TCSS, MNSI, SWM and VPT-QST are analyzed using cross tabulation. Area under receiver operating characteristic (ROC) curve analysis was used to measure diagnostic accuracy of each tools. SPSS 19.0 was used for statistical analysis.Results: TCSS had a sensitivity, specificity, positive predictive value, negative predictive value positive likelihood ratio, negative likelihood ratio, and accuracy as much as: 70%, 97%, 97%, 74%, 23,33, 0,28 and 83%. The result of TCSS analysis using ROC showed that TCSS had excellent diagnostic value with AUC (Area Under Curve) of 0.89 (95%CI 82%-96,5%). The AUC of BPNS score, monofilamen and VPT-QST respectively: 0,469, 0,194, and 0,189.Conclusion: The result of the HIV-DSP diagnostic test using TCSS score has the best value compared to other tools.